Antifungal Mechanisms and Application of Lactic Acid Bacteria in Bakery Products: A Review - Liu, Aiping; Xu, Ruixia; Zhang, Shun; Wang, Yuting; Hu, Bin; Ao, Xiaolin; Li, Qin; Li, Jianlong; Hu, Kaidi; Yang, Yong; Liu, Shuliang (Frontiers in Microbiology, 2022)
Bakery products are nutritious, but they are susceptible to fungal contamination, which leads to a decline in quality and safety. Chemical preservatives are often used to extend the shelf-life of bakery products, but long-term consumption of these preservatives may increase the risk of chronic diseases. Consumers increasingly demand food with fewer chemical preservatives. The application of lactic acid bacteria (LAB) as a novel biological preservative not only prolongs the shelf-life of bakery products, but also improves the baking properties of bakery products. This review summarizes different types and action mechanisms of antifungal compounds produced by LAB, factors affecting the production of antifungal compounds, and the effects of antifungal LAB on bakery products, providing a reference for future applications of antifungal LAB in bakery products.